Investigation of dual-sensitive nanogels based on chitosan and N-isopropylacrylamide and its intelligent drug delivery of 10-hydroxycamptothecine. (18th August 2015) - Wang, Yajing; Wang, Jiu; Xu, Hongjiang; Ge, Liang; Zhu, Jiabi
Abstract: The work was to prepare and characterize a responsive drug delivery system built of chitosan-g-poly ( N -isopropylacrylamide) (CTS-g-PNIPAAm) nanogels and to evaluate the effects of CTS molecular weight (Mw) on the loading and in vitro release of insoluble drug 10-hydroxycamptothecine (HCPT). The CTS-g-PNIPAAm copolymers were synthesized by radical polymerization. The Mw and physical chemistry properties such as diameter, second virial coefficient of grafted PNIPAAm were investigated by dynamic and static laser light scattering method. A series of cross-linked CTS-g-PNIPAAm nanogels were prepared with N, N′ -methylenebisacrylamide initially added as a cross-linker. The thermal and pH-sensitive features of cross-linked CTS-g-PNIPAAm nanogels were studied by determining the variance of transmittance, changeable size and reversed zeta potential. The critical aggregation concentrations (CAC) of resultant nanogels decreased from 0.045 to 0.036 mg/mL with CTS Mw increased from 50 kDa to 700 kDa. The loading efficiency of the HCPT encapsulated into CTS-g-PNIPAAm nanogels increased in parallel with CTS Mw, while the cumulative release percentage of HCPT-loaded nanogels decreased with CTS Mw increasing at both 25 °C and 37 °C. Fitting results of HCPT release data to different mathematical models suggested a diffusion-controlled mechanism at 25 °C. However, the release behaviors were dominated by combined effects of polymer erosion and osmotic pressure driven at 37 °C. The cytotoxicity study of the CTS-g-PNIPAAm nanogels against hepatic L02 cells indicated that the resultant nanogels did not exhibit apparent cytotoxicity.